Rancang Bangun Sistem Pakar Penentuan Kepribadian - Hardianto, Roki; Kusuma, Chandra (Jurnal Sistem Komputer dan Informatika (JSON), 2019)
With the development of technology every time, all lines of life are computerized. Likewise, an expert system for determining personality types can help psychologists complete their tasks quickly, precisely and easily. Besides the lack of psychologists in handling cases of personality type analysis is an important note why an expert-based expert determination system is needed. In this study an expert system that was built using a desktop interface can also be based online. Not only when you meet a psychologist you can use it, but you can also use anyone using a PC or smartphone. This research uses the Case Based Reasoning method, where this method is a suitable method in the formulation of new knowledge of the examination of patients in the field of psychology. Referring to a study conducted by Florence Littauer who divided personality types into 4 parts namely Melancholy, Saguinis, Koleris and Plegmatis. It is hoped that this research can help patients and psychologists in analyzing and determining their personality precisely, quickly and easily